PERANCANGAN APLIKASI e-SCM PADA PT CAHAYA BUANA FURINDOTAMA - Honni, Honni; Herman, Robertus Tang; Christanto, Erick (Bina Nusantara University, 2008)
PT Cahaya Buana Furindotama is a company incorporated in the Olympic Group. This company is a manufacturingcompany which produces furniture and household-wares made from plastic material. Problems en countered were rawmaterial shortage and production delay, though the company already had a partnership with several suppliers because ofthe un-integrated data and there was a â€œhuman errorâ€ in data entry. Results of the problem were the company could losemarket share and threatened with competitorsâ€™ position. Based on the problems which arose, it was proposed to use an e-SCMapplication system at the company because e-SCM application system could help the company to manage flow of raw materialbetter and strengthen the companyâ€™s relationship between suppliers and distributors. The methods used were Porterâ€™s FiveForces to analyze the companyâ€™s position in market and SWOT Method to determine a strategy could be used by the company.Based on the internal matrix (IFE), the result obtained was 3:08. Whereas, the external matrix (EFE), the result obtained was3:34. Based on both results, it can be concluded that the company is in a strong position in matrix IE. Whereas, the strategyused is Strengths-Opportunity (SO) which is in SWOT matrix. It is expected that the SO strategy and e-SCM applicationsystem, the company can be more strength its position in the market.Keywords: e-SCM, SWOT, internal matrix, external matrix